A study on implementing the coronial system in Malaysia upon custodial deceased of the detainee. / Hazwani Zahari … [et al.] - Zahari, Hazwani; Hairiri, Mohammad Muzammil; Hassan, Nadia Shazwani; Abidin, Nursyafiqah (2013)
The importance of having the coronial system in Malaysia is to uphold the human rights as we all know the human rights are the essential rights and can become a sensitive issue to every country in this world. The objectives of this research are to provide an avenue to the family members of the deceased detainee to seek justice, to investigate the importance and the need of coronial system in our country and also to recommend the coronial system in Malaysia. Coronial system is an ancient system that has been practiced by many countries up until today. By having the independent coroner court, it will give justice to the deceased who died during detention or in custody of the state, particularly in the police as well as other enforcement agencies' custody. It also gives the satisfaction to the family of the deceased and also to the public who question the manner of the death of the deceased. Besides that, by having the independent court in our country it will ensure that every custodial death will be investigated in a thorough and proper manner. This research further seeks guidance from several notable countries such as the United Kingdom, Australia, Germany, New Zealand, England and Wales, which practice the coronial system in order to initiate the same system in Malaysia.